The Role of Information and Communication Technologies in Civil Law Relations: Analysis of the Civil Code of the Republic of Kazakhstan (Law, State and Telecommunications Review, 2021)
[Purpose] The purpose of the study is to establish using the methods of legal linguistics, synthesis and analysis of information the mechanism of formation of the conceptual sphere of cybersecurity and its representation in the texts of regulations.[Methodology] The methodological basis of the study was determined by the hermeneutic approach to jurisprudence which is mainly focused on methodology, legal technique, the logical and semantic interpretation of certain provisions of various branches of law. In the process of research, methods of analysis and synthesis of information, the comparative analysis also were used.[Findings] The authors note that the use of the system of civil law relations affects both the civil sphere directly and the procedural aspects of relations and partially the criminal branch of law. The synergistic nature of informatisation of civil law relations and consider it as a part of the system of general cybersecurity of the state as a whole were emphasized. The use of this concept and its legal construction was revealed.[Practical Implications] The practical significance of the study is determined by the possibility of forming an integrated system of using the mechanism for predicting the development of information and communication technologies to form an equilibrium environment for ensuring the rule of law.[Originality] The novelty of the study is determined by the fact that information and communication technologies are understood as components of a larger system of ensuring legal security in a country as a whole.